Exploring preferences of different modes of administration of hypomethylating agent treatments among patients with acute myeloid leukemia - Delmas, Audrey; Batchelder, Laurie; Arora, Ira; Bayet, Solene; Bruhn, David; Eberhardt, Alice; Philpott, Stephanie; Rodriguez-Leboeuf, Ana Maria (Frontiers in Oncology, 2023)
Introduction About half of patients with Acute Myeloid Leukemia (AML) are unsuitable for Standard Induction Chemotherapy (SIC). Hypomethylating Agents (HMAs) intravenously (IV) or subcutaneously (SC) in a clinical setting are typically offered as an alternative. However, injectable HMAs may be too burdensome for patients given the frequent hospital visits and side effects. This study explored patient treatment preferences for different modes of administration (MOA) and the relative importance of treatment-related characteristics that influence treatment decisions. Methods Semi-structured 1:1 interviews were conducted with 21 adult patients with AML in Germany, the United Kingdom (UK), and Spain, who had experience with HMAs or were scheduled to be treated with HMAs. After discussing their experience of living with AML and its treatments, patients were presented with hypothetical treatment scenarios to explore their preferences, and a ranking exercise to assess the relative importance of treatment characteristics that influence their treatment-decisions for AML. Results Most patients reported an overall preference for oral administration over parenteral routes (71%), mostly due to convenience. Those preferring IV or SC routes (24%) reasoned with faster speed of action and closer onsite monitoring. When presented with a hypothetical situation of a patient having to choose between two AML treatments that were identical except for their MOA, the majority preferred the oral route (76%). Regarding treatment characteristics that influence their treatment decision, patients most frequently reported efficacy (86%) and side effects (62%) as important followed by mode of administration (29%), daily life impacts (24%) and location of treatment (hospital versus home) (14%). However, only efficacy and side effects were rated as number one deciding factors (67% and 19%, respectively). Patients most frequently rated dosing regimen (33%) as least important. Conclusion The insights gained from this study may help support patients with AML who are receiving HMA treatment instead of SIC. A potential oral HMA with similar efficacy and tolerability profiles to injectable HMAs could influence treatment decisions. Furthermore, an oral HMA treatment might decrease the burden of parenteral therapies and improve patients’ overall quality of life. However, the extent of influence MOA has on treatment decisions requires further investigation.